Pascal's negative image of sociality - Shamrai , Viktoria (Sententiae, 2000)
The author states the negative nature of Pascal's attitude towards the theories of natural law and social contract due to their fundamental inability to offer a positive maxim of human behavior. Author argues that one of the grounds for Pascal's criticism is that the theories of social contract and natural law rather fix and cement the negative aspects of man manifested in his natural state. Reconstructing the deeper foundations of this critique, the author argues that it is rather not Christianity in itself, but the existential spirit of Pascal's philosophy that makes him an opponent to the idea of the social contract and determines his negative position towards sociality. Pascal does not create a teaching in the field of social philosophy that can become an alternative to the social contract theory. His thoughts are characterized by the author rather as notes in the margins of the latter. These notes clearly show a line of criticism and a tendency towards the rejection of sociality, which is opposed to the social constructivism of the last two centuries of European history.